MRI efficacy in diagnosing internal lesions of the knee: a retrospective analysis. - Nikolaou, Vassilios S; Chronopoulos, Efstathios; Savvidou, Christianna; Plessas, Spyros; Giannoudis, Peter; Efstathopoulos, Nicolas; Papachristou, Georgios (J Trauma Manag Outcomes, 2008)
BACKGROUND: Many surgeons tend to believe that MRI is an accurate, non invasive diagnostic method, enough to lead to decisions for conservative treatment and save a patient from unnecessary arthroscopy. We conducted a retrospective study to investigate the accuracy of the MRI of the knee for the detection of injuries of the meniscus, cruciate ligaments and articular cartilage, in comparison with the preoperative clinical examination and intraoperative findings. Between May 2005 and February 2006 102 patients after clinical examination were diagnosed with meniscal or cruciate injury and underwent definitive treatment with arthroscopy. 46 of these patients fulfilled the inclusion criteria. The accuracy, sensitivity, specificity, negative and positive predictive values of the MRI findings were correlated with the lesions identified during arthroscopy. The diagnostic performance of the initial clinical examination was also calculated for the meniscal and cruciate ligament injuries. RESULTS: The accuracy for tears of the medial, lateral meniscus, anterior and posterior cruciate ligaments and articular cartilage was 81%, 77%, 86%, 98% and 60% respectively. The specificity was 69%, 88%, 89%, 98% and 73% respectively. The positive predictive value was 83%, 81%, 90%, 75% and 53% respectively. Finally, the clinical examination had significant lower reliability in the detection of these injuries. CONCLUSION: MRI is very helpful in diagnosing meniscal and cruciate ligament injuries. But in a countable percentage reports with false results and in chondral defects its importance is still vague. The arthroscopy still remains the gold standard for definitive diagnosis.